(3GdGcJSGH aj JdNjU cJH GdCfSGHs - (3GHf GdNjVQj , eMeO Hf eMeO Hf YHO Gddg Hf NjVQ GdRHjOj, bWH GdOjf CHh GdNjQ,J (B894 (3g` s ((3HGdeOQSI HMGQI HgGA GdOjf HGdbGgQI s)
(3ChdgG (B:s
(3HMQa GdaGA hdG COQi Ggi GdJi jbGd dgG GdaGHMGf Ce ZjQgG s
(3BNQgG (B:s
(3GdHjLi Cf jLYd Pdc NGdU dhLgg GdcQje hCf jfaY Hg WdGHg jefg hcQeg GdeQMhe GHf GdSOGO s
(3hdbO dNU ajg CfSGH GdSeYGfi hVe Edjg eG YfO GHf GdCKjQ hGdQTGWis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B237s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B116 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B27 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs